2012
DOI: 10.1183/09031936.00222911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autoimmune diseases on risk and survival in histology-specific lung cancer

Abstract: Patients with autoimmune diseases are at an increased risk of cancer due to underlying dysregulation of the immune system or treatment. Data on cancer incidence, mortality and survival after autoimmune diseases would provide further information on the clinical implications.We systematically analysed data on lung cancer in patients diagnosed with 33 different autoimmune diseases. Standardised incidence ratios (SIRs), standardised mortality ratios (SMRs) and hazard ratios (HRs) were calculated for subsequent inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“…Cancer risk is elevated in patients with obesity; in patients with diabetes and resulting insulin resistance and chronic hyperinsulinemia;4649 and in patients with inherited, acquired (eg, from HIV/AIDS), or drug-induced (eg, from treatment with steroids or biologics) immunosuppression 50,51. Some of these risk factors also may be associated with rate of cancer growth and cancer grade/differentiation and thus with prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer risk is elevated in patients with obesity; in patients with diabetes and resulting insulin resistance and chronic hyperinsulinemia;4649 and in patients with inherited, acquired (eg, from HIV/AIDS), or drug-induced (eg, from treatment with steroids or biologics) immunosuppression 50,51. Some of these risk factors also may be associated with rate of cancer growth and cancer grade/differentiation and thus with prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…in a study involving 7624 SLE patients identified from the Swedish Hospital Discharge Registry demonstrated an even higher incidence of all forms of lung cancer (SIR 2.47, 95% CI, 1.97, 3.05)[33], and they delineated the rates of specific histologic types of lung malignancies in SLE patients. The risk was most significantly increased for small cell lung cancer (SIR 3.38, 95% CI, 1.89, 5.59), followed by squamous cell carcinoma (SIR 2.97, 95% CI, 1.86, 4.50), large cell carcinoma (SIR 2.55, 95% CI, 1.53, 3.99), and adenocarcinoma (SIR 2.12, 95% CI, 1.34, 3.18) [33]. The SMR was also increased for small cell lung cancer in SLE patients (SMR 2.69, 95% CI, 2.11, 3.38), suggesting increased mortality in SLE patients with this form of lung cancer [33].…”
Section: Lung Malignanciesmentioning
confidence: 99%
“…A history of a few specific autoimmune diseases has been found to increase mortality in patients with certain digestive tract cancers [17], but does not seem to influence prognosis in other cancer types, e.g., lung cancer [18]. In a large study on patients with Hodgkin lymphoma, a prior diagnosis of autoimmune disease was associated with poorer survival [25].…”
Section: Introductionmentioning
confidence: 99%